2016
DOI: 10.1007/s00381-016-3215-y
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal (fetal and neonatal) astrocytoma: a review

Abstract: Introduction The purpose of this review is to document the various types of astrocytoma that occur in the fetus and neonate, their locations, initial findings, pathology, and outcome. Data are presented that show which patients are likely to survive or benefit from treatment compared with those who are unlikely to respond. Materials and methods One hundred one fetal and neonatal tumors were collected from the literature for study. Results Macrocephaly and an intracranial mass were the most common initial findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 80 publications
(242 reference statements)
0
24
0
1
Order By: Relevance
“…According to one review, of all childhood brain tumors, the ones diagnosed within the first 2 months after birth account for approximately 0.5–1.5% of patients (Rickert, ). In a literature review of 101 fetal and neonatal patients of astrocytoma, 9.9% were low grade astrocytoma located at the spinal cord (half of patients), cerebral hemisphere ( n = 3), and optic nerve ( n = 2; Isaacs, ). The role of PRMT7 in tumorigenesis is highlighted in a recently published article describing arginine methylation in B cell histones by PRMT7 (Ying et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…According to one review, of all childhood brain tumors, the ones diagnosed within the first 2 months after birth account for approximately 0.5–1.5% of patients (Rickert, ). In a literature review of 101 fetal and neonatal patients of astrocytoma, 9.9% were low grade astrocytoma located at the spinal cord (half of patients), cerebral hemisphere ( n = 3), and optic nerve ( n = 2; Isaacs, ). The role of PRMT7 in tumorigenesis is highlighted in a recently published article describing arginine methylation in B cell histones by PRMT7 (Ying et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These tumors are composed of glial cells (astrocytes) of varying degrees of differentiation. The most common fetal astrocytic tumor is the highly malignant glioblastoma multiforme (GBM), but other variants may also be seen, including low‐grade or anaplastic astrocytoma, and desmoplastic infantile astrocytoma 27,28 . Most fetal astrocytomas present as a large supratentorial mass causing shift of midline structures, obstructive hydrocephalus, and macrocrania 1,2,28 .…”
Section: Astrocytomamentioning
confidence: 99%
“…Low‐grade astrocytoma, represented by congenital hypothalamic chiasmatic glioma, appears as a focal suprasellar lesion without aggressive features. Glial tumors are most often detected at the end of the third trimester, which is later in gestation than other CNS tumors 1,28 ; however, they may grow very rapidly in a surprisingly short period of time. Isaacs presents a comprehensive analysis of fetal astrocytoma with an emphasis on prenatal management and prognostication for these patients, as well as suggestions for postnatal treatment based on potential for survival 28 .…”
Section: Astrocytomamentioning
confidence: 99%
“…2 Pooled data from 101 cases of perinatal astrocytic lesions have shown that high-grade gliomas (HGG), particularly glioblastomas, are the most common glial tumors in this population. 3 ALK protein is highly conserved in humans and has a major role in fetal neural cell development and differentiation. 5 Rearrangements involving ALK were initially identified in anaplastic large B-cell non-Hodgkin lymphomas.…”
Section: Perinatal Complex Low-and High-grade Glial Tumor Harboring Amentioning
confidence: 99%
“…These tumors usually account for 0.5‐1.5% of all brain tumors in children . Pooled data from 101 cases of perinatal astrocytic lesions have shown that high‐grade gliomas (HGG), particularly glioblastomas, are the most common glial tumors in this population . Yet, the simultaneous occurrence of mixed high‐grade and low‐grade gliomas (MHLG) may be considered exceptional.…”
mentioning
confidence: 99%